The HUBUNGAN HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK DI RSUD Dr. H ABDUL MOELOEK BANDAR LAMPUNG: Hemodialisis, Kualitas Hidup, Pasien Gagal Ginjal Kronik - Amartya, Salwa Anastasya; Yulendasari , Rika; Sary, Lolita; Hermawan , Dessy (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: In Indonesia, projections indicate that the count of individuals suffering from kidney failure is set to rise from 19,612 to 100,000 between 2014 and 2019. The occurrence of those receiving hemodialysis, both seasoned and newcomers, from January to October 2024, reached 255 new patients alongside 352 longstanding patients. However, data concerning the quality of life for chronic kidney failure patients undergoing Hemodialysis therapy is currently nonexistent and has yet to be uncovered.Purpose: It's recognized that a connection exists between hemodialysis (in terms of duration/time, frequency, and length of HD therapy) and the quality of life of patients with chronic kidney failure.Methods: This study employs a quantitative research methodology utilizing an observational design framed within a cross-sectional approach. The population considered for this investigation was gathered from January through October 2024, with a total of 255 patients, out of which the sample comprised 156 newly diagnosed chronic kidney failure patients receiving hemodialysis. The method of sampling applied was accidental sampling. The research instrument utilized is the quality of life assessment (WHOQOL-BREF), which consists of 25 items. The analysis conducted includes both univariate and bivariate analyses, utilizing the Spearman rank test.Results: Findings from the study indicated that the majority of participants underwent hemodialysis for a duration of ≥3 hours per session, totaling 143 respondents (91.7%). The majority received hemodialysis twice a week, comprising 117 respondents (75.0%). Moreover, most of the respondents had been undergoing hemodialysis for a period of 12-24 months, totaling 69 respondents (44.2%), and a significant number reported a favorable quality of life, amounting to 48 respondents (30.8%). Statistical tests utilizing the Spearman rank test for the duration/time of HD in relation to quality of life yielded a p-value of 0.001.